Dieback of apricot plantations caused by 'Ca. Phytoplasma prunorum' in Borsod-Abaúj-Zemplén county (Northern-Hungary) - Tarcali, Gábor; Kiss, Emese; Kövics, György J.; Süle, Sándor; Irinyi, László; Kiss, László (Acta Agraria Debreceniensis, 2010)
Plant diseases caused by phytoplasmas have increasing importance in all over the world for fruit growers. Lately, phytoplasma diseases occur on many fruit varieties and responsible for serious losses both in quality and quantity of fruit production. In the long-run these diseases cause destruction of fruit trees. The apricot phytoplasma disease (Ca. Phytoplasma prunorum) was first reported in Europe in 1924 from France. In 1992 the disease has also been identified in Hungary. On the base of growers' signals serious damages of "Candidatus Phytoplasma prunorum" Seemüller and Schneider, 2004 (formerly: European stone fruit yellows phytoplasma) could be observed in different stone fruit plantations in the famous apricot-growing area nearby Gönc town, Northern-Hungary. Field examinations have been begun in 2009 in several stone fruit plantations in Borsod-Abaúj-Zemplén County mainly in Gönc region which is one of the most important apricot growing regions in Hungary, named “Gönc Apricot Growing Area”. Our goals were to diagnose the occurrence of Ca. Phytoplasma prunorum on stone fruits (especially on apricot) in the North-Hungarian growing areas by visual diagnostics and confirm data by laboratory PCR-based examinations. All the 28 collected samples were tested in laboratory trials and at 13 samples from apricot, peach, sour cherry and wild plum were confirmed the presence of phytoplasma (ESFY). On the base of observations it seems evident that the notable losses caused by "Ca. Phytoplasma prunorum" is a new plant health problem to manage for fruit growers, especially apricot producers in Hungary.